A Non-Classical Marketing Approach for Classical Music Performing Organizations: Enhancing Marketing Strategies for Classical Music Performing Organizations (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Over the most recent two decades, traditional music performing crafts manship associations have been excitedly hunting down approaches to pull in more youthful groups of onlookers and upgrade participation at their live shows. It appears that their established promoting approaches are not accomplishing their objectives, and another and more forceful approach is altogether. The investigation overviewed a specimen of 664 grown-up people in the Inland Empire district of Southern California with respect to their participation examples to, states of mind towards, and inclinations for traditional music shows when all is said in done and Riverside County Philharmonic exhibitions specifically. Discoveries were investigated and suggestions were made for traditional music performing associations to upgrade their showcasing procedures and strategies.